Geschlechterspezifische Unterschiede bei der endovaskulären Behandlung der peripheren arteriellen Verschlusskrankheit – Eine systematische Literaturübersicht - Behrendt, C. -A.; Rother, Ulrich; Ruemenapf, G.; Uhl, C.; Boeckler, D.; Goertz, H.; Heidemann, F. (Gefässchirurgie, 2020)
Background: There is evidence for gender disparities in the development, diagnostics and treatment of symptomatic peripheral arterial occlusive disease (PAOD). Although women represent 50% of treated cohorts in the literature, they only make up a small proportion in randomized trials on PAOD. Up to now, guidelines have included hardly any gender-sensitive recommendations and the results of observational studies are contradictory. This systematic literature review is aimed at identifying available observational studies on gender differences in the endovascular treatment of symptomatic PAOD. Materials and Methods: A systematic review of the literature was carried out using PubMed, focusing on retrospective observational studies comparing outcomes between men and women. Results: A total of 37 articles were identified, constituting a cohort of 5,489,558 patients of both genders (40.3% women). Propensity score matching was used in five studies to address confounders. Twenty-three studies reported outcomes beyond the index hospital stay and 30 days, respectively. While 10 studies were able to identify disadvantages in females, 6 studies reported disadvantages in men. A further 21 studies were not able to identify any clear disparities. Conclusions: Owing to methodological limitations and the inadequate comparability of the studies included, the available real-world evidence does not allow any distinct conclusions regarding gender-specific disparities in the endovascular treatment of PAOD.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Endovascular techniques; Gender; Health care research; Quality indicator; Real world evidence